Evaluation of Ultimate Strength of Reinforced Concrete Beams Strengthened with FRP Sheets under Torsion - Ma, Shengqiang; Bunnori, N. Muhamad; Kok, Keong Choong (EDP Sciences, 2016)
The ultimate torque of reinforced concrete (RC) members strengthened with fiber reinforced polymer (FRP) sheets does not only depend on the torque of RC members, but also on the FRP contribution to the torque. For structural design, predicting the accurate torsional capacity of the strengthened beams is considerably important. Three existing models for calculating the ultimate torsional moment of RC beams and two existing models for computing the FRP contribution to the ultimate torque are described and combined. Based on an experimental database collected from existing literature, six combinations were discussed and evaluated from the calculative values compared with the experimental results. The comparison shows that the combination of ACI 318 and fib Bulletin 14 models (Group 2), as well as Chinese and Ghobarah models (Group 6), can reasonably and accurately predict the ultimate torque of beams strengthened with FRP sheet. Furthermore, the ultimate torque of six boxsection beams strengthened with fully wrapping or U-wrap calculated by the Group 6 shows closely to the experimental results.